Application of the Consolidated Framework for Implementation Research to examine nurses' perception of the task shifting strategy for hypertension control trial in Ghana - Joyce Gyamfi; John P. Allegrante; Juliet Iwelunmor; Olajide Williams; Jacob Plange-Rhule; Sarah Blackstone; Michael Ntim; Kingsley Apusiga; Emmanuel Peprah; Gbenga Ogedegbe (BMC, 2020)
Abstract Background The burden of hypertension in many low-and middle-income countries is alarming and requires effective evidence-based preventative strategies that is carefully appraised and accepted by key stakeholders to ensure successful implementation and sustainability. We assessed nurses' perceptions of a recently completed Task Shifting Strategy for Hypertension control (TASSH) trial in Ghana, and facilitators and challenges to TASSH implementation. Methods Focus group sessions and in-depth interviews were conducted with 27 community health nurses from participating health centers and district hospitals involved in the TASSH trial implemented in the Ashanti Region, Ghana, West Africa from 2012 to 2017. TASSH evaluated the comparative effectiveness of the WHO-PEN program versus provision of health insurance for blood pressure reduction in hypertensive adults. Qualitative data were analyzed using open and axial coding techniques with emerging themes mapped onto the Consolidated Framework for Implementation Research (CFIR). Results Three themes emerged following deductive analysis using CFIR, including: (1) Patient health goal setting- relative priority and positive feedback from nurses, which motivated patients to make healthy behavior changes as a result of their health being a priority; (2) Leadership engagement (i.e., medical directors) which influenced the extent to which nurses were able to successfully implement TASSH in their various facilities, with most directors being very supportive; and (3) Availability of resources making it possible to implement the TASSH protocol, with limited space and personnel time to carry out TASSH duties, limited blood pressure (BP) monitoring equipment, and transportation, listed as barriers to effective implementation. Conclusion Assessing stakeholders' perception of the TASSH implementation process guided by CFIR is crucial as it provides a platform for the nurses to thoroughly evaluate the task shifting program, while considering the local context in which the program is implemented. The feedback from the nurses informed barriers and facilitators to implementation of TASSH within the current healthcare system, and suggested system level changes needed prior to scale-up of TASSH to other regions in Ghana with potential for long-term sustainment of the task shifting intervention. Trial registration Trial registration for parent TASSH study: NCT01802372. Registered February 27, 2013.